Physiological responses of avicennia marina var. acutissima and Bruguiera parviflora under simulated rise in Sea Level - Rasheed, M.Z.; Normaniza, O.; Rozainah, M.Z. (Universiti Kebangsaan Malaysia, 2013)
Climate change components such as increased in atmospheric carbon dioxide (CO2) and rising sea levels are likely to affect mangrove ecosystems. Healthy mature propagules of A. marina var. acutissima and B. parviflora were subjected to two tidal treatments; shallow and deep; for six months. Shallow treatment mimicked the current tidal fluctuations and deep treatment simulated future tidal conditions under rise in sea level. Deep treatment decreased Amax of both species and significant two way interactions between tidal treatments and species were observed. A400 was significantly reduced in the deep treatment in B. parviflora but not in A. marina. Carbon dioxide compensation point was not affected by the tidal treatments but varied significantly between both species. The ratio A400/Amax was significantly lower in the shallow treatment in B. parviflora indicating higher carbon sink potential at moderate tidal flooding whereas A400/Amax of A. marina was less variable between tidal treatments. Chlorophyll conductance was insensitive to tidal flooding but was significantly higher in B. parviflora than in A. marina. Carbon sequestration of B. parviflora was substantially reduced in the deep treatment while the difference between tidal treatments was much less in A. marina. These results indicated that these two species responded differently under tidal flooding where A. marina was less sensitive to tidal. Thus, A. marina is better adapted to the projected climate change than B. parviflora.